The Transformation to Professional Management at Pardee Homes - McGee, Michael; Flamholtz, Eric; Schreiner, Kathryn (Senate Hall, 2005)
This article presents a case study of the transition of Pardee Homes from an entrepreneurship to a professionally managed firm. It examines changes in leadership, planning processes, and organizational structure involved in the completion of a transformation from a family owned business to a professionally managed firm. It focuses in particular upon the changes in organizational structure over a period of more than a decade. These changes were a key component of the overall transformation process. The case demonstrates the practical difficulties involved in the application of the theoretical constructs of organizational structure in the real world.
Keywords: transformation|professional management|organizational structure|organizational success|management systems